2014
DOI: 10.1093/cid/ciu937
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Correlates, and Outcomes of Cryptococcal Antigen Positivity Among Patients With AIDS, United States, 1986–2012

Abstract: The prevalence of cryptococcal infection among advanced AIDS patients in the United States was high and above the published cost-effectiveness threshold for routine screening. We recommend routine CrAg screening among human immunodeficiency virus-infected patients with a CD4 count ≤100 cells/µL to detect and treat early infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 33 publications
2
55
5
Order By: Relevance
“…The overall prevalence of positive serum CrAg in the present study is similar to that reported by other authors in Uganda, with a prevalence rate of 8.8%, among patients with a CD4+ cell count <100 cells/mL [12]. These prevalence rates are lower than to those from Cambodia and South Africa among patients with similar demographic characteristics [17,18] and are three times greater than those reported from the United States, using the same assessment methods [19]. …”
Section: Discussionsupporting
confidence: 88%
“…The overall prevalence of positive serum CrAg in the present study is similar to that reported by other authors in Uganda, with a prevalence rate of 8.8%, among patients with a CD4+ cell count <100 cells/mL [12]. These prevalence rates are lower than to those from Cambodia and South Africa among patients with similar demographic characteristics [17,18] and are three times greater than those reported from the United States, using the same assessment methods [19]. …”
Section: Discussionsupporting
confidence: 88%
“…In Ecuador according to MSP 3,546 new AIDS cases were recorded in 2014. Another analysis found the prevalence of cryptococcal antigenemia is 2.9%, among HIV patients [10].…”
Section: Methodsmentioning
confidence: 98%
“…Some data suggest a ‘screen and treat’ would be cost effective, even in resource-rich settings, although this is currently not part of standard practice, despite recent reports of CrAg prevalence of more than 3% in the United States. 176,182 Routine screening for cryptococcal infection and/or prophylaxis are not recommended in solid organ transplant recipients, even when immunosuppression is augmented in patients with previously (appropriately) treated infection. 183 …”
Section: Treatmentmentioning
confidence: 99%